Porcupine inhibition enhances hypertrophic cartilage differentiation - Killinger, Michael; Szotkowská, Tereza; Lusková, Denisa; Zezula, Nikodém; Bryja, Vítězslav; Buchtová, Marcela (JBMR plus, 2025)
Porcupine (PORCN) is a membrane-bound protein of the endoplasmic reticulum, which modifies Wnt proteins by adding palmitoleic acid. This modification is essential for Wnt ligand secretion. Patients with mutated PORCN display various skeletal abnormalities likely stemming from disrupted Wnt signaling pathways during the chondrocyte differentiation. To uncover the mechanism of PORCN action during chondrogenesis, we used 2 different PORCN inhibitors, C59 and LGK974, in several model systems, including micromasses, 3D cell cultures, long bone tissue cultures, and zebrafish animal model. PORCN inhibitors enhanced cartilaginous extracellular matrix (ECM) production and accelerated chondrocyte differentiation, which resulted in the earlier induction of cellular hypertrophy as well as cartilaginous mass expansion in micromass cultures and cartilaginous organoids. In addition, both PORCN inhibitors expanded the hypertrophic zone and reduced the proliferative zone in the growth plate. This led to a significant increase in cartilaginous tissue and ultimately resulted in the elongation of tibias in the mouse organ cultures. Also, LGK974 treatment of Danio rerio embryos induced expansion of craniofacial cartilage width together with the shortening of the body axis, which was consistent with a phenomenon occurring upon inhibition of non-canonical Wnt signaling. By combining PORCN inhibition with exogenous Wnt proteins activating either canonical/β-catenin (WNT3a) or non-canonical (WNT5a) signaling, we propose that the key mechanism mediating pro-chondrogenic effects of PORCN inhibition is the removal of canonical ligands that prevent chondrocyte differentiation. In summary, our results provide evidence of the distinct role of PORCN in both the early and late stages of cartilage development. Further, our data demonstrate that PORCN inhibitors can be used in the experimental and clinical strategies that need to trigger chondrocyte differentiation and/or cartilage outgrowth.
Keywords: chondrogenesis; tibia; micromass cultures; cartilage; porcupine; orofacial anomalies; Wnt; jaw hypoplasia; hypertrophy